2017
DOI: 10.5935/1414-8145.20170018
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of healthcare professionals regarding the assessment and treatment of neonatal pain

Abstract: Objectives: To describe and analyze the attitudes of health professionals in relation to the evaluation and treatment of pain in newborns undergoing painful procedures in neonatal units. Methods: This descriptive, exploratory, quantitative study was performed in a maternity hospital in the state of Rio de Janeiro. Participants were 42 nursing assistants/technicians, 22 nurses, 20 physicians and 02 physical therapists. Data were collected through a self-administered questionnaire covering the profile of the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…In a study by Christoffel et al (2017), with the objective of describing and analyzing the attitudes of health professionals regarding the evaluation and treatment of pain in the newborns submitted to painful procedures in the neonatal unit, the authors showed that most of the sample studied prefer to use the facilitated tucking position prior to the procedure.For these authors, the facilitated tucking technique helps the self-regulation of the newborn during painful and stressful procedures, with the principle of maintaining a comfortable position. It is known that interventions of a non-pharmacological nature, which include changing the baby's position, nesting it, facilitated tucking, maintaining the flexed position and simply holding it, help managing and self-regulation of these newborns when acute pain makes itself present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Christoffel et al (2017), with the objective of describing and analyzing the attitudes of health professionals regarding the evaluation and treatment of pain in the newborns submitted to painful procedures in the neonatal unit, the authors showed that most of the sample studied prefer to use the facilitated tucking position prior to the procedure.For these authors, the facilitated tucking technique helps the self-regulation of the newborn during painful and stressful procedures, with the principle of maintaining a comfortable position. It is known that interventions of a non-pharmacological nature, which include changing the baby's position, nesting it, facilitated tucking, maintaining the flexed position and simply holding it, help managing and self-regulation of these newborns when acute pain makes itself present.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that interventions of a non-pharmacological nature, which include changing the baby's position, nesting it, facilitated tucking, maintaining the flexed position and simply holding it, help managing and self-regulation of these newborns when acute pain makes itself present. However, wrapping up itself is not effective to reduce pain from moderate to severe pain procedures (Christoffel et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some strategies are used for pain relief, but without standardization or systematization of the actions. In a Brazilian study, the absence of protocols and guidelines that use validated scales and pharmacological and nonpharmacological measures for a systematized neonatal pain relief based on evidences for pain assessment was also observed (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies show gaps between the health professionals' knowledge and practice for the management of pain in newborns and, in general, the use of analgesic measures is poor or insufficient (4) .…”
Section: Introductionmentioning
confidence: 99%